Mitochondria in innate immune signaling - Banoth, Balaji; Cassel, Suzanne L. (Translational research : the journal of laboratory and clinical medicine, 2018)
Mitochondria are functionally versatile organelles. In addition to their conventional role of meeting the cell's energy requirements, mitochondria also actively regulate innate immune responses against infectious and sterile insults. Components of mitochondria, when released or exposed in response to dysfunction or damage, can be directly recognized by receptors of the innate immune system and trigger an immune response. In addition, despite initiation that may be independent from mitochondria, numerous innate immune responses are still subject to mitochondrial regulation as discrete steps of their signaling cascades occur on mitochondria or require mitochondrial components. Finally, mitochondrial metabolites and the metabolic state of the mitochondria within an innate immune cell modulate the precise immune response and shape the direction and character of that cell's response to stimuli. Together, these pathways result in a nuanced and very specific regulation of innate immune responses by mitochondria.